Divisive Jus Cogens Reloaded. Some Remarks on the Peremptory Character of Self determination under the ICJ Advisory Opinion of 19 July 2024 (Polish Yearbook of International Law, 2025)
The article focusses on a specific aspect of the International Court of Justice’s (ICJ) 2024 Advisory Opinion on the legal consequences arising from the policies and practices of Israel in the Occupied Palestinian Territory, namely the statement that the right to self-determination constitutes a peremptory norm of international law. The article submits that the finding of the ICJ can be at variance with the basic criteria set forth by the International Law Commission in the 2022 Conclusions on identification and legal consequences of peremptory norms of general international law (jus cogens). In particular, limiting the peremptory effect of self-determination to cases of foreign occupation that lead to annexation risks undermining the unitary, universal character of peremptory rules. Overall, the case confirms the divisive potential of the concept of jus cogens in the international legal community.